2015
DOI: 10.2147/jaa.s74178
|View full text |Cite
|
Sign up to set email alerts
|

The past, present, and future of monoclonal antibodies to IL-5 and eosinophilic asthma: a review

Abstract: Asthma is a heterogeneous syndrome that might be better described as a constellation of phenotypes or endotypes, each with distinct cellular and molecular mechanisms, rather than as a singular disease. One of these phenotypes is eosinophilic asthma. As the development of eosinophilic inflammation is categorically dependent on the biological activity of Interleukin (IL)-5, IL-5 antagonism became an obvious target for therapy in this phenotype. Early trials of monoclonal antibodies targeting the biological activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 51 publications
0
7
0
1
Order By: Relevance
“…Over production of Th2 cytokines is one of the features of allergic diseases and some other inflammations 29. IL-5 is the key cytokine to promote the development of eosinophils 30. The present data add novel information to the characteristics of IL-5; IL-5 not only regulates eosinophil development, but it also regulates mast cell activities by inducing the expression of Bcl2L12 in mast cells.…”
Section: Discussionmentioning
confidence: 59%
“…Over production of Th2 cytokines is one of the features of allergic diseases and some other inflammations 29. IL-5 is the key cytokine to promote the development of eosinophils 30. The present data add novel information to the characteristics of IL-5; IL-5 not only regulates eosinophil development, but it also regulates mast cell activities by inducing the expression of Bcl2L12 in mast cells.…”
Section: Discussionmentioning
confidence: 59%
“…Three different biologic drugs targeting IL-5 signaling are available, and FDA-approved. All three treatments have been consistently shown to reduce blood eosinophil counts and sputum eosinophils ( 47 , 52 , 53 ). Mepolizumab is a humanized IgG1 monoclonal antibody that recognizes and blocks IL-5 and prevents its binding to IL-5 receptor alpha subunit (IL-5Rα or CD125) on the surface of eosinophils.…”
Section: Conventional Treatments That Target Th2-type Inflammation Inmentioning
confidence: 95%
“…[6] and their study that indicated that dyspnoea is a better predictor of 5-year survival than measures of airways obstruction in patients with COPD. In eosinophilic asthmatics, mepolizumab has been shown to improve exacerbation rates but does not show any consistent effect on objective measures such as FEV 1 [7, 8]. O. Usmani referenced the clinical utility of forced vital capacity (FVC) (measured during the same manoeuvre as FEV 1 ).…”
Section: “Pro/con” Debate On Current and Evolving Tests In Lung Functionmentioning
confidence: 99%